If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1) + -14 = 6 Reorder the terms: 2(-1 + x) + -14 = 6 (-1 * 2 + x * 2) + -14 = 6 (-2 + 2x) + -14 = 6 Reorder the terms: -2 + -14 + 2x = 6 Combine like terms: -2 + -14 = -16 -16 + 2x = 6 Solving -16 + 2x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 2x = 6 + 16 Combine like terms: -16 + 16 = 0 0 + 2x = 6 + 16 2x = 6 + 16 Combine like terms: 6 + 16 = 22 2x = 22 Divide each side by '2'. x = 11 Simplifying x = 11
| 5(1+2n)+6(n-3)=8n-5n | | (3x+8)=(5x-12) | | 7-3x=7+2(6-x) | | -5(3-7n)=90 | | 8x-12+x=-4x-3 | | -11+-16= | | 2z-5=3z-4 | | -14+15=m-7 | | -6(x+1)=6-5x | | 36+36-18= | | ln(1-3x)+C=ln(x)+C | | 81x^2+18x+6=equation | | 7x+1=9x+(-17) | | 10-16x-6-5x=7 | | -15=-4m+5[5] | | .16(y-3)+.04=.14y-.03(30) | | x+(x*.20)+(x*.10)=5000 | | 12x+1=11x+3 | | 23-p=8 | | 6+5(-7+7v)=146 | | w^2+8w-9=0 | | x+(x-6)=116 | | 10+6=-2(7x-8) | | 85=5(1+4n) | | 12x+9-4x-4=7-x+30 | | 4x+37-6x=3-8x+4 | | 4(3x+7)=-17+21 | | 2(6n+1)=62 | | -8+3x-4=5x+10 | | 12x+4=11x+11 | | 6(3-z)*5=-z | | 9=4p+6-p |